Prevalence of overweight and associated factors in under-five-year-old children in urban population in Brazil - Müller,Rosângela de Mattos (2014)
Objectives: To estimate the prevalence of overweight in children under five years old from urban households and to investigate associated factors. Methods: Cross-sectional population-based study carried out in the five regions of Brazil with a sample of 6,397 children. The World Health Organization 2006 Growth Curves were used and children were considered overweight when Z-score was higher than two standard deviations of weight for height. The following variables were investigated: family income, mothers' education level, race, age, gender, number of siblings, weight at birth and duration of exclusive breastfeeding. Proportions were compared with the χ2 test and reasons of prevalence were calculated. Logistic regression was used for the adjusted analysis. Results: The prevalence of overweight was of 12%. After adjustments, this prevalence was significantly higher among males (p = 0.030) and inversely proportional to the child's age (p = 0.032). White children presented 22% higher overweight prevalence than non-white ones. A linear direct association was verified between weight at birth and overweight (p = 0.000). Children who were breastfed until 120 days presented 34% more prevalence of overweight when compared to the ones who were breastfed for a longer time. Conclusions: Overweight prevalence was higher in male, under one year old, white children, with more than 3,500 grams of weight at birth and who were exclusively breastfed until 120 days.